Interdisciplinary management of Class III malocclusion with cleft lip and palate - Retno Iswati; Cendrawasih Andusyana Farmasyanti; Aulia Ayub; Anne Marie Kuijpers-Jagtman; Ananto Ali Alhasyimi (Dental Journal, 2023)
Background: A cleft lip and palate (CLP) is one of the most common birth defects of the face. Individuals with CLP often have a significant growth disturbance of the maxilla along three dimensions, resulting in skeletal Class III malocclusion and cross bite. Oral rehabilitation can be complicated. Purpose: The purpose of this case study was to highlight the necessity of sequential interdisciplinary management to improve facial esthetics and correct functional disturbances for a patient with CLP. Case: The patient was a 20-year-old woman complaining of the unpleasant appearance of her upper front teeth. She had a concave profile with Class III skeletal patterns (SNA: 78O; SNB: 82O; ANB: -4O), cleft lip and palate, and an anterior and posterior crossbite. Case Management: A combined orthodontic, endodontic, conservative, periodontic, and prosthetic approach was proposed to achieve normal occlusion, function, and a harmonious profile. The combination of rapid maxillary expansion and fixed orthodontics (standard edgewise appliance) established good general alignment and a Class I relationship. After 15 months of treatment, both the posterior and anterior crossbite had been completely corrected. In order to address the gingival margin differences, the patient was instructed to make another appointment with the periodontist and was referred to the restorative dentist for veneer restorations and the prosthodontist for fabrication of a removable retainer with obturator. Conclusion: This interdisciplinary approach greatly improved both esthetics and function. The patient was satisfied with the results achieved.